Sports leadership : a reference guide - Dodds, Mark; Reese, James T., Jr., 1966-; McRay, Jeni (Santa Barbara, California : Mission Bell Media, 2015)
Included in this volume: Leadership Glossary: Essential Terms for the 21st Century, Jeni McRay, Editor. This contemporary, informative and authoritative supplemental text covers more than 975 essential leadership terms from an interdisciplinary perspective. -- from back cover.
Place of publication from publisher's website.
Includes bibliographical references and index.
Keywords: Athletes -- Psychology; Coaching (Athletics) -- Psychological aspects; Sports -- Psychological aspects; Leadership